Mitochondria-associated endoplasmic reticulum membranes (MAMs) and their role in glaucomatous retinal ganglion cell degeneration—a mini review - Pham, Jennifer H.; Stankowska, Dorota L. (Frontiers in Neuroscience, 2023)
Glaucoma is a leading cause of blindness worldwide, commonly associated with elevated intraocular pressure (IOP), leading to degeneration of the optic nerve and death of retinal ganglion cells, the output neurons in the eye. In recent years, many studies have implicated mitochondrial dysfunction as a crucial player in glaucomatous neurodegeneration. Mitochondrial function has been an increasingly researched topic in glaucoma, given its vital role in bioenergetics and propagation of action potentials. One of the most metabolically active tissues in the body characterized by high oxygen consumption is the retina, particularly the retinal ganglion cells (RGCs). RGCs, which have long axons that extend from the eyes to the brain, rely heavily on the energy generated by oxidative phosphorylation for signal transduction, rendering them more vulnerable to oxidative damage. In various glaucoma models, mitochondrial dysfunction and stress from protein aggregates in the endoplasmic reticulum (ER) have been observed in the RGCs. However, it has been shown that the two organelles are connected through a network called mitochondria-associated ER membranes (MAMs); hence this crosstalk in a pathophysiological condition such as glaucoma should be evaluated. Here, we review the current literature suggestive of mitochondrial and ER stress related to glaucoma, indicating potential cross-signaling and the potential roles of MAMs.